F59 Huntington's disease young adult study (HD-YAS). (September 2018) - Zeun, Paul; Lowe, Jessica; Osborne-Crowley, Katie; O'Callaghan, Claire; Johnson, Eli; Gregory, Sarah; Nair, Akshay; Fayer, Kate; Rodrigues, Filipe; Estevez-Fraga, Carlos; Wild, Ed; Zhang, Gary; et al.
Abstract : HD-YAS will study a cohort of young adult HD Gene Expansion Carriers (HDGEC) decades before expected symptom onset to characterize the very earliest signs of disease-related brain changes and identify whether there is any identifiable early functional impairment. Currently there is no detailed characterization of such a young adult HDGEC cohort and this represents the earliest time point after predictive genetic testing in which to gain disease insights. HD-YAS will be important in determining the earliest potential time window for therapeutic intervention. HD-YAS will recruit 120 participants-60 premanifest HDGECs and 60 gene negative or family controls-and will use a cross-sectional comparison with one visit per participant to assess the earliest time-point at which neurodegeneration can be detected. Participants will undergo 3T Volumetric MRI, rsfMRI and task fMRI, NODDI, and cognitive assessments including the CANTAB and EMOTICOM batteries, and biosamples such as CSF, blood and DNA will be collected to investigate biomarkers. Participants will be 18–40 years old and at-risk individuals must have a predictive genetic test; either carry the HD gene (gene-carrier) or not carry the HD gene (control). Individuals must not show any clinical symptoms of HD, have a disease burden score of ≤240, and must be willing and able to comply with the study visit and study procedures. HD-YAS began in August 2017 and is expected to complete by February 2019. HD-YAS collaborates with Enroll-HD, UK clinical genetics services and HD charity groups to identify potentially eligible participants throughout the UK. HD-YAS is funded by Wellcome, with CSF collection funded by CHDI. HD-YAS investigators – Participant Identification Site Investigators; Dr Oliver Quarrell, Dr Nayana Lahiri, Dr Andrea Nemeth, Dr Mary Porteous, Dr Elisabeth Rosser, Dr David Craufurd, Dr Rhona MacLeod, Dr Deborah Ruddy, Dr Roger Barker, Dr Simon Holden, Dr Hugh Rickards, Dr Anne Rosser, Dr Emma Hobson, Prof Angus Clarke, Dr Katherine Lachlan, Dr Reza Kiani, Dr Timothy Harrower. Thank you to the HDA, HDYO, SHA.